Kinetics and Dose Dependency of Intranasal Oxytocin Effects on Amygdala Reactivity - Spengler, Franny B.; Schultz, Johannes; Scheele, Dirk; Essel, Maximiliane; Maier, Wolfgang; Heinrichs, Markus; Hurlemann, René (Biological psychiatry (1969), 2017)
Current neuroimaging perspectives on a variety of mental disorders emphasize dysfunction of the amygdala. The neuropeptide oxytocin (OXT), a key mediator in the regulation of social cognition and behavior, accumulates in cerebrospinal fluid after intranasal administration in macaques and humans and modulates amygdala reactivity in both species. However, the translation of neuromodulatory OXT effects to novel treatment approaches is hampered by the absence of studies defining the most effective dose and dose–response latency for targeting the amygdala. To address this highly relevant issue, a total of 116 healthy men underwent functional magnetic resonance imaging using a randomized, double-blind, placebo-controlled crossover study design. The experimental rationale was to systematically vary dose–test latencies (15–40, 45–70, and 75–100 minutes) and doses of OXT (12, 24, and 48 international units) in order to identify the most robust effects on amygdala reactivity. During functional magnetic resonance imaging, subjects completed an emotional face recognition task including stimuli with varying intensities ranging from low (highly ambiguous) to high (less ambiguous). Our results indicate that the OXT-induced inhibition of amygdala responses to fear was most effective in a time window between 45 and 70 minutes after administration of a dose of 24 international units. Furthermore, the observed effect was most evident in subjects scoring high on measures of autistic-like traits. Behavioral response patterns suggest that OXT specifically reduced an emotional bias in the perception of ambiguous faces. These findings provide initial evidence of the most effective dose and dose–test interval for future experimental or therapeutic regimens aimed at targeting amygdala functioning using intranasal OXT administration.